IL-6 expression regulates tumorigenicity and correlates with prognosis in bladder cancer. - Miao-Fen Chen; Paul-Yang Lin; Ching-Fang Wu; Wen-Cheng Chen; Chun-Te Wu (PLoS ONE, 2013)
Identification of potential tumor markers will help stratify and identify a tumor's malignant potential and its response to specific therapies. IL-6 has been reported to be a predictor in various cancers. Therefore, the present study was performed to highlight the role of IL-6 in improving treatment and determining prognosis of bladder cancer. The human bladder cancer cell lines HT1376 and HT1197 were selected for cell and animal experiments, in which biological changes after experimental manipulation of IL-6 were explored, including tumor behavior and related signaling in bladder cancer. In addition, clinical specimens from 85 patients with muscle-invasive, and 50 with non-muscle invasive bladder cancers were selected for immunohistochemical staining to evaluate the predictive capacity of IL-6 in relation to clinical outcome. The data revealed that IL-6 was overexpressed in the bladder cancer specimens compared with non-malignant tissues at both mRNA and protein levels. Positive staining of IL-6 was significantly correlated with higher clinical stage, higher recurrence rate after curative treatment, and reduced survival rate. Tumor growth and invasive capability were attenuated when IL-6 was blocked. The underlying changes included decreased cell proliferation, less epithelial-mesenchymal transition (EMT), decreased DNA methyltransferase 1 expression and attenuated angiogenesis. In conclusion, our findings showed that IL-6 could be a significant predictor for clinical stage and prognosis of bladder cancer. Moreover, targeting IL-6 may be a promising strategy for treating bladder cancer.